Suprasegmental Elements In Kakawin - Simpen, I Wayan; Bagus Rai Putra, Ida; Permana Mahardika, I Putu; Iye, Risman (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
Kakawin is a traditional literary work that belongs to the sekar agung category, which has characteristics and traits distinct from sekar madya and sekar alit. Kakawin is marked by the presence of guru and laghu in each of its meters. Guru and laghu are the guidelines that must be followed by anyone performing or reading a kakawin literary work. Guru refers to a word or syllable that undergoes a change during its performance. These changes can include elongation, a shift from low to high pitch or vice versa, or a change in emphasis from loud to soft or the opposite. In short, guru is always marked by a change in sound. On the other hand, laghu does not experience a change in sound during its performance. The sounds and their accompanying elements, such as guru and laghu, are studied using phonological theory. Research findings show that there are several forms of characters used to write kakawin as markers of guru and laghu.